A dual‐band wide‐angle polarization‐insensitive ultrathin gigahertz metamaterial absorber. Issue 7 (26th April 2013) - Zhai, Huiqing; Li, Zhenhua; Li, Long; Liang, Changhong
Abstract In this research, a dual‐band ultrathin metamaterial absorber with wide‐angle and polarization‐insensitive characteristic is presented. The metamaterial absorbers consist of a periodic arrangement of two scales of Jerusalem resonators and a metallic background plane, separated by only 0.8 mm dielectric spacer. By changing the direction of polarization, we achieve that the structure is polarization insensitive. Simulations demonstrate two good absorption rates in the designed frequency bands over wide angles of incident waves for both transverse electric and magnetic polarizations. Waveguide experiments are conducted to verify that the proposed designs can achieve two good absorptivity peaks. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1606–1609, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27622